Influence Of Doppler Ultrasound On Fetal Activity - Murrills, A. J.; Barrington, P.; Harris, P. D.; Wheeler, T. (British medical journal (Clinical research ed.), 1983)
A randomised and double blind study of 100 subjects and 50 controls was performed to confirm or refute a report from Cardiff in 1975 that continuous Doppler ultrasound, as used in fetal heart rate monitoring, increases fetal movement by over 90%. The results showed such an effect to be most unlikely (power>0.99). A total of 150 pregnant mothers recorded fetal movements for 30 minutes while connected to a specially modified cardiotocograph, the ultrasound being switched on at random for either the first or second 15 minutes in 100 of the patients. The mean difference in 15 minute movement count, with and without ultrasound, among the 100 patients was 0.2 of a movement (SD 12.7; p>0.6 by two tailed Wilcoxon matched pairs signed ranks test). The control group showed a mean difference of 2.6 movements (SD 12.1; p>0.2). Results of a pilot study suggested that the observations in the earlier report may have been influenced by mechanisms unrelated to ultrasound.